2004
DOI: 10.1111/j.1540-8159.2004.00541.x
|View full text |Cite
|
Sign up to set email alerts
|

Syndrome of Inappropriate Antidiuretic Hormone Secretion Induced by Amiodarone Therapy

Abstract: We describe a case of amiodarone induced hyponatremia consistent with the syndrome of inappropriate antidiuretic hormone (SIADH) that developed during amiodarone loading, similar to three prior reports. The hyponatremia improved after a lower maintenance dose was initiated. This episode was reported online to the FDA (http://www.fda.gov/medwatch), and future amiodarone labeling will include SIADH as a potential side effect (personal communication, Wyeth Medical Science). Clinicians should be aware of this rare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…In 1996, the first case of amiodarone-induced hyponatremia was reported [5]. Since then, a total of 10 cases of amiodarone-induced SIADH have been published in the literature (table 1; [6, 7, 8, 9, 10, 11, 12, 13]).…”
Section: Discussionmentioning
confidence: 99%
“…In 1996, the first case of amiodarone-induced hyponatremia was reported [5]. Since then, a total of 10 cases of amiodarone-induced SIADH have been published in the literature (table 1; [6, 7, 8, 9, 10, 11, 12, 13]).…”
Section: Discussionmentioning
confidence: 99%
“…A review of the literature revealed four case reports of SIADH‐induced hyponatremia associated with amiodarone treatment between 1999 and 2004. In two of them, hyponatremia developed during the loading dose of amiodarone treatment and responded well to dose reduction without discontinuation of drug (1, 2). In one of these cases, the serum Na level was improved within 3 weeks of dose reduction (1).…”
mentioning
confidence: 99%
“…One of the patients who was managed only with dose reduction developed recurrence of hyponatremia after reloading with amiodarone. 12 In that case, the hyponatremia improved and eventually resolved again after resuming the previous dose of amiodarone.…”
Section: Discussionmentioning
confidence: 87%
“…In the published medical literature, only 17 cases of amiodarone-induced hyponatremia have been reported, to our knowledge (Table 3). [8][9][10][11][12][13][14][15][16][17][18][19][20][21] The affected patients were predominantly male (n = 13) and elderly (range: 58-88 years, median: 68 years). Either atrial fibrillation or ventricular arrhythmia was the indication to start amiodarone in all 17 cases.…”
Section: Discussionmentioning
confidence: 99%